PREDICTION OF ACADEMIC ACHIEVEMENT IN OBLIGATORY COMPULSORY EDUCATION AND BACCALAUREATE STUDENTS THROUGH THE MILLON ADOLESCENT CLINICAL INVENTORY - Broc Cavero, Miguel Ángel; Gil Ciria, Carmen (Anales de Psicología / Annals of Psychology, 2008)
The progressive increase of the conflicting in the classrooms, the behavior problems among students and teachers and the increasing appearance of personality disorders, added to a bigger academic failure in some groups of adolescents joined to social and familiar dysfunctions have done posed us, from a clinical and psychopatological perspective, a research basically correlational multivariable with binary logistic regression techniques, intending to found initial relationships between personality and educational (achievement) variables. About 380 students of Compulsory Secondary Education (ESO – 12 to 16, and Baccalaureate –16 to 19 years) were administered the Millon Adolescents Clinical Inventory (and other materials) as well as academic performance measures.